MAP VISUALIZATION IN ARCGIS AND MAPINFO - K. R.Khakimova; M. A. Ergasheva; N. M. Gulomjonova; Kh. Kh. Sharofiddinova (Galaxy International Interdisciplinary Research Journal, 2022)
Map production, also called cartography, is one of the processes of visual representation of reality. This practice has long been of great interest to humanity and was originally a craft [1-3]. Today, most maps are produced by computers and are often the last step in GIS analysis - the way the result is presented. This makes knowledge of map production important and relevant when working with various GIS analyses.